We are never meeting in real life : essays - Irby, Samantha (Faber & Faber, 2019)
With heartfelt candor and her usual side-splitting bite, humorist, essayist, and blogger at bitchesgottaeat.com Samantha Irby captures powerful emotional truths while chronicling the disaster that has been her life. An ill-fated pilgrimage and romantic vacation to Nashville to scatter her estranged father's ashes, awkward sexual encounters, a Bachelorette application gone awry, and more-- sometimes you just have to laugh, even when your life is a dumpster fire.